Study of Physical and Physiological Parameters in Aeroponic Cultivation of Iceberg Lettuce (Lactuca Sativa var. Capitata) - Gorliczay, Edit; Montvai, Kornélia; Tamás, János; Szabó, András; Nagy, Attila (GEORGIKON FOR AGRICULTURE, 2024)
Soilless cultivation systems, such as aeroponics, are gaining increasing attention. Aeroponics allows plants to grow without soil and is particularly beneficial for leafy greens like iceberg lettuce (Lactuca sativa var. capitata, ’Great lakes 118’), which require rapid growth and good nutrient supply. Our research aimed to determine the cultivation parameters for iceberg lettuce in aeroponic systems, focusing on nutrient solution intensity. In our experiment, we grew iceberg lettuce for 5 weeks in a closed climate chamber with four different nutrient solution intensities: 10x15 min/day, 8x8 min/day, 4x15 min/day, and 2x30 min/day. Weekly measurements included leaf number, stress parameters (Fv/Fm, Fv/Fo), SPAD value, and final measurements of head weight, root length, and root mass. Results showed that nutrient solution intensity did not significantly affect leaf number, but photosynthetic efficiency and relative chlorophyll content varied. Higher daily nutrient solution (10x15min/day) resulted in greater head weight, root mass, and root length. Therefore, higher daily nutrient solution intensity is recommended for the aeroponic cultivation of iceberg lettuce.
Keywords: aeroponics; soiless crop production; iceberg lettuce